Patients with chronic ankle instability exhibit increased sensorimotor cortex, dorsolateral prefrontal cortex, and superior temporal gyrus activation during single-leg stance: a functional near-infrared spectroscopy study - Xie, Huimin; Li, Xuejiao; Wang, Zihan; Gao, Yan; Zhang, Lining (Frontiers in Human Neuroscience, 2026)
IntroductionBalance deficits are associated with clinical manifestations in patients with chronic ankle instability (CAI); however, evidence of cortical plasticity related to balance control remains insufficient. This study aimed to evaluate cortical activity and balance differences between patients with CAI and healthy individuals during single-leg stance, with or without vision, and to explore the correlations between brain blood flow signals and homeostatic function to elucidate the neurophysiological changes in balance control.MethodsThis cohort study involved 30 patients with CAI from a single hospital and 30 age-matched healthy controls. Cortical activity in the sensorimotor cortex (SMC), dorsolateral prefrontal cortex (DLPFC), and superior temporal gyrus (STG) was measured using functional near-infrared spectroscopy. The activity ranges of the center of mass (COM), acceleration, and acceleration extremes were calculated using wearable inertial sensors. Moreover, scale assessments (visual analog scale, foot and ankle ability measure, and Cumberland Ankle Instability Tool) and functional tests (classical balance, Y-balance, multi-directional reach tests, and timed up-and-go tests) were conducted.ResultsSignificant between-group effects were observed for the root mean square (RMS) centroid acceleration in the anteroposterior (AP) direction (F = 5.51, p = 0.02), whereas within- and between-group differences existed for RMS centroid acceleration in the mediolateral (ML) direction (F = 3.56, p = 0.03; F = 8.5, p = 0.004). Significant within- and between-group differences were identified for peak acceleration magnitude (Acc_max) –AP (F = 7.85, p = 0.001; F = 11.83, p = 0.001) and Acc_max–ML (F = 15.64, p = 0.0001; F = 5.06, p = 0.026). The oxyhemoglobin concentration change (ΔHbO2) was significantly greater in patients with CAI than in healthy controls during single-leg stance; between-group differences were identified in the STG–right cerebral hemisphere (R) (F = 10.25, p = 0.002), DLPFC–R (F = 50.99, p = 0.001), SMC–R (F = 27.48, p = 0.0001), STG–left cerebral hemisphere (L) (F = 13.6, p = 0.0001), DLPFC–L (F = 24.21, p = 0.0001), and SMC–L (F = 29.75, p = 0.0001); within-group differences in the SMC–L (F = 9.92, p = 0.0001); and interaction effects in the STG–R (F = 5.73, p = 0.004). During right-leg stance with the eyes closed, RMS–ML and Acc_max–ML exhibited a high positive correlation with ΔHbO2 in the STG–L (RMS–ML: p = 0.001, r = 0.72; Acc_max–ML: p = 0.001, r = 0.74).ConclusionPatients with CAI exhibited lower balance ability and greater COM bias than healthy controls, with increased bilateral activation in brain regions, regardless of which limb was elevated; the results were more pronounced with vision inhibited. Enhanced brain activity was positively correlated with COM changes. Functional near-infrared spectroscopy and wearable inertial sensors can detect balance in patients with CAI.